Spells, Herbs, and Islam in the Influenza Medicine from the Tetamba Book - Fika Hidayani; Am'mar Abdullah Arfan (JURNAL PENELITIAN, 2025)
In the cultural heritage of the archipelago, incantations function not only as healing incantations or prayers, but also as a medium that combines material elements in the form of natural ingredients and spiritual elements in the form of prayers and suggestions of faith. This study aims to reveal the harmony between the Islamic archipelago and local culture in traditional health practices recorded in the Kitab Tetamba from Cirebon, a 16th century manuscript containing various herbal recipes and incantations as means of healing. The present study employs a descriptive method by analysing the text, with a particular focus on the section about influenza treatment in the Tetamba Book, to interpret the cultural meaning and spiritual values contained therein. The analysis demonstrates that the treatment system outlined in the manuscript is holistic in nature, integrating the utilisation of medicinal plants with the belief that authentic healing is divinely facilitated by Allah SWT. This practice can be considered as a harmonious acculturation between local traditions and Islamic values, where cultural elements function practically while the spiritual dimension serves as a philosophical foundation. The Tetamba book is a historical artefact that reflects the cultural and spiritual identity of the people of the archipelago in the realm of traditional medicine.